Identification of endophytic fungi on the leaves of Rhyzophora stylosa Griff mangrove in the coastal area of Bokonusan Semau Village - Rafael, Andriani; Sabuna, Alan Charis; Manifani, Derven (Universitas Labuhanbatu, 2024)
Rhyzophora stylosa Griff is a mangrove plant that grows on the coast of Bokunusan village, Semau District, Kupang Region. Endophyte fungi are found in plant tissues and can function as agents for controlling pathogenic pests. The purpose of this research was to isolate and identify endophyte fungi found in the young and mature leaf of R. stylosa Griff at the Mangrove forest, Bokunusan Village, Semau District, East Nusa Tenggara. This research was conducted from November to December 2023 at the Microbiology Laboratory; Biology Study Program, Aretha Wacana Christian University. The method used was the Potato Dextrose Agar (PDA) media and fungal identification based on macroscopic and microscopic characteristics. Based on the results of the study, nine isolate was isolated from young and mature leaf of R. stylosa Griff. Two endophyte fungi were obtained from R. stylosa Griff leaves. The endophyte fungi found were genus Aspergillus and Trichoderma.